Crop residue/Livestock relationships - Sandford, S.G. (International Crops Research Institute for the Semi-Arid Tropics, 1989)
Reviews crop and livestock relationships in the farming systems of the semi arid zones. Discusses the effects of cropping on livestock output and effects of livestock on crop output. Also looks into crop output, wealth in the form of livestock and household consumption. Ends with a discussion on crops and livestock complementarity and competition.